Analysis of crack defects in the hanger welding area using the DMAIC method in the heavy equipment industry - Rahayu Budi Prahara; Nur Imam; Indra Setiawan (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
Heavy Equipment Industry is a company operating in the mining heavy equipment industry. The Quality Control Department continues to strive to maintain and improve the quality of every product produced. During 2022 there were complaints from customers, where there were 7 complaints about hangers detaching from the frame. The hanger is a connecting component between the leaf spring and the chassis which functions as a support for the load. This has a very fatal impact because it is related to safety, unit function and unit productivity. The crack defect caused a repair process by re-welding the part of the hanger where the crack was present. The aim of this research is to reduce the defect rate in Hanger defects. The method used is DMAIC. Primary data and supporting data were collected through field observations to describe actual conditions before repairs. Based on the results of the analysis and improvements that have been carried out, it was found that creating work instructions for the process of attaching hangers to units can help manpower understand the process and work sequence in hanger fabrication. The proposal to add reinforcement check points to the hanger setting check sheet is hoped to be able to maintain the hanger without reinforcement entering the next process and increase supervision of the hanger welding quality.